2012
DOI: 10.3109/02656736.2011.644620
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparison of simultaneous versus sequential injection technique for thermochemical ablation in a porcine model

Abstract: Thermochemical ablation produced substantial volumes of coagulated tissues relative to the amounts of reagents injected, considerably greater than acid alone in either technique employed. The largest volumes were obtained with sequential injection, yet this came at a price in one case of cardiac arrest. Simultaneous injection yielded the highest recorded temperatures and may be tolerated as well as or better than acid injection alone. Although this pilot study did not show a clear advantage for either sequenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Selective delivery to the target tumor is achieved via localized application and is not affected by the hostile tumor environment (low blood flow, interstitial hypertension, low pH) that limits the efficacy of radiation therapy and chemotherapy. TCA using a 10 M combination of acid and base has been shown sufficient to coagulate a 18.9-ml volume of blood perfused tissue in vivo animal models [10]. Further, by-products of the reaction create a locally toxic high salt concentration environment that may synergistically increase the diameter of the lethal zone of this therapy as well as serve as a local diffusion reservoir to decrease the risk of local recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective delivery to the target tumor is achieved via localized application and is not affected by the hostile tumor environment (low blood flow, interstitial hypertension, low pH) that limits the efficacy of radiation therapy and chemotherapy. TCA using a 10 M combination of acid and base has been shown sufficient to coagulate a 18.9-ml volume of blood perfused tissue in vivo animal models [10]. Further, by-products of the reaction create a locally toxic high salt concentration environment that may synergistically increase the diameter of the lethal zone of this therapy as well as serve as a local diffusion reservoir to decrease the risk of local recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Although initial efforts established the concept of TCA [10,11], a better understanding of the fundamental mechanisms of cell death resulting from combined hyperthermal and hyperosmotic stresses implemented in vivo is needed to optimize delivery protocols. Salts are frequently added to proteins in solution to manipulate either biomolecular stability or ligand-binding affinity [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work assessed the suitability of various acid and base combinations and concentrations in terms of their thermal profile and ease of handling in phantom ( 12 , 13 ) and ex vivo ( 14 , 15 ) models. Using acetic acid (AcOH) and sodium hydroxide (NaOH) as acid and base reagents, respectively, feasibility was demonstrated using in vivo porcine liver models, in which TCA resulted in larger coagulation volumes than those achieved with delivery of acid or base alone ( 16 , 17 ). Although early studies showed promising results, the paucity of data in tumor models and high-quality imaging for quantitative image-guided delivery limits the understanding of TCA.…”
mentioning
confidence: 99%